A Comparative Analysis of Transaction Efficiency and Customer Satisfaction Based on Digital and Non-Digital Payment Systems in SMEs - Moh Fakhri Siddiqi; Nur Fajria (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
Technological advancement has driven changes in SME payment systems, shifting from non-digital methods toward digital payments. However, not all business operators adopt digital payments, as differences in technology readiness, business characteristics, and the habits of SME operators and customers have caused both methods to remain in use. This study aims to compare digital and non-digital payments in SMEs and analyze their effects on transaction efficiency and customer satisfaction. A qualitative method with a phenomenological approach was employed to understand SME operators’ direct experiences using both payment methods. Data were collected through in-depth interviews, direct observation, and documentation, then analyzed using thematic analysis. The results indicate that digital payments are superior in transaction efficiency due to automated processes; in contrast, non-digital payments show inconsistent efficiency owing to manual processes, purchase quantities, and customer volume. In terms of customer satisfaction, no single payment method comprehensively improves satisfaction; rather, satisfaction is limited to specific customer groups and is influenced by customer habits and digital literacy. These findings constitute the study’s novelty, indicating that payment system success in SMEs is not solely determined by technology use, but also by the characteristics of the customers served. Accordingly, this study suggests that offering both digital and non-digital payments simultaneously is the most effective strategy for SMEs to meet diverse customer needs.